Analysis of Actual Versus Predicated Intracranial Volume Changes for Distraction Osteogenesis Using Virtual Surgical Planning in Patients With Craniosynostosis. Issue 3 (May 2021) - Kamel, George N.; Carbulido, Mary Kristine; McKee, Ryan M.; Segal, Rachel M.; Ewing, Emily; Brandel, Michael G.; Lance, Samuel H.; Gosman, Amanda A.
Abstract : Introduction: The primary outcome metric in patients with craniosynostosis are changes in intracranial volumes (ICVs). In patients who undergo distraction osteogenesis (DO) to treat craniosynostosis, changes are also dependent on the length of distraction. Virtual surgical planning (VSP) has been used to predict anticipated changes in ICV during cranial vault reconstruction. The purpose of this study is to analyze the actual versus predicted ICV changes using VSP in patients who undergo DO for craniosynostosis management. Methods: All patients with craniosynostosis treated with DO at a single institution, Rady Children's Hospital, between December 2013 and May 2019 were identified. Inclusion criteria are as follows: VSP planning with predicted postoperative ICV values and preoperative and postdistraction CT scans to quantify ICV. Postoperative ICV and VSP-estimated ICV were adjusted for age-related ICV growth. The primary outcome measure calculated was age-adjusted percent volume change per millimeter distraction (PVCPD), and results were analyzed using paired Wilcoxon signed rank tests. Results: Twenty-seven patients underwent DO for cranial vault remodeling. Nineteen patients were nonsyndromic, and 8 patients were syndromic. The median postoperative PVCPD was 0.30%/mm, and the median VSP-estimated PVCPD was 0.36% per millimeter ( P < 0.001). A subanalysis of nonsyndromic patients showed a median postoperative PVCPD of 0.29%/mm in nonsyndromic patients that differed significantly from the VSP estimate of 0.34%/mm ( P = 0.003). There was also a significant difference in syndromic patients' observed PVCPD of 0.41%/mm versus VSP estimate of 0.79%/mm ( P = 0.012). Conclusions: Virtual surgical planning overestimates the change in ICV attributable to DO in both syndromic and nonsyndromic patients.